Human engineered heart tissue transplantation in a guinea pig chronic injury model. (May 2022) - von Bibra, Constantin; Shibamiya, Aya; Geertz, Birgit; Querdel, Eva; Köhne, Maria; Stüdemann, Tim; Starbatty, Jutta; Schmidt, Felix N.; Hansen, Arne; Hiebl, Bernhard; Eschenhagen, Thomas; Weinberger, Florian
Abstract: Myocardial injury leads to an irreversible loss of cardiomyocytes (CM). The implantation of human engineered heart tissue (EHT) has become a promising regenerative approach. Previous studies exhibited beneficial, dose-dependent effects of human induced pluripotent stem cell (hiPSC)-derived EHT patch transplantation in a guinea pig model in the subacute phase of myocardial injury. Yet, advanced heart failure often results from a chronic remodeling process. Therefore, from a clinical standpoint it is worthwhile to explore the ability to repair the chronically injured heart. In this study human EHT patches were generated from hiPSC-derived CMs (15 × 10 6 cells) and implanted epicardially four weeks after injury in a guinea pig cryo-injury model. Cardiac function was evaluated by echocardiography after a follow-up period of four weeks. Hearts revealed large transmural myocardial injuries amounting to 27% of the left ventricle. EHT recipient hearts demonstrated compact muscle islands of human origin in the scar region, as indicated by a positive staining for human Ku80 and dystrophin, remuscularizing 5% of the scar area. Echocardiographic analysis demonstrated no significant functional difference between animals that received EHT patches and animals in the cell-free control group (fractional area change 36% vs. 34%). Thus, EHT patches engrafted in the chronically injured heart but in contrast to the subacute model, grafts were smaller and EHT patch transplantation did not improve left ventricular function, highlighting the difficulties for a regenerative approach. Graphical abstract: Unlabelled Image Highlights: Engineered heart tissue patches engrafted in the chronically injured heart. Human cardiomyocyte grafts were smaller than after transplantation in a subacute injury model. Graft size was insufficient to restore heart function.